Precision Control of High Speed Drives using Active Vibration Damping - Gordon, Daniel (University of Waterloo, 2010)
In order to meet industry demands for improved productivity and part quality, machine tools must be equipped with faster and more accurate feed drives. Over the past two decades, research has focused on the development of new control strategies and smooth trajectory generation techniques. These developments, along with advances in actuator and sensor technology, have greatly improved the accuracy of motion delivery in high speed machine tools. However, further advancement is limited by the vibration of the machine’s structure. The purpose of the research in this thesis is to develop new control techniques that use active vibration damping to achieve bandwidths near the structural frequencies of machine tools, in order to provide better dynamic positioning of the tool and workpiece. Two machine tool drives have been considered in this study. The first is a precision ball screw drive, for which a pole-placement technique is developed to achieve active vibration damping, as well as high bandwidth disturbance rejection and positioning. The pole-placement approach is simple and effective, with an intuitive physical interpretation, which makes the tuning process straightforward in comparison to existing controllers which actively compensate for structural vibrations. The tracking performance of the drive is improved through feedforward control using inverted plant dynamics and a novel trajectory pre-filter. The pre-filter is designed to remove tracking error artifacts correlated to the velocity, acceleration, jerk and snap (4th derivative) of the commanded trajectory. By applying the least-squares method to the results of a single tracking experiment, the pre-filter can be tuned quickly and reliably. The proposed controller has been compared to a controller used commonly in industry (P-PI position-velocity cascade control), and has achieved a 40-55 percent reduction in peak errors during tracking and machining tests. The controller design, stability analysis, and experimental results are discussed. The second drive considered is a linear motor driven X-Y stage arranged as a T-type gantry and worktable. The worktable motion is controlled independently of the gantry using a loop shaping filter. The gantry is actuated by dual direct drive linear motors and is strongly coupled to the worktable position, which determines its inertial characteristics. A 94 Hz yaw mode is handled in the gantry control law using sensor and actuator averaging, and active vibration damping. The stability and robustness of the design are considered using multivariable frequency domain techniques. For the worktable motion along the gantry, a bandwidth of 130 Hz is achieved. The gantry crossover frequency is 52 Hz, which is 3 times higher than the bandwidth that can be achieved using independent PID controllers (16 Hz). The performance of the proposed control scheme has been verified in step disturbance (i.e., rope snap) tests, as well as tracking and contouring experiments.
Keywords: Control; Active Damping; Mechanical Engineering